The use of propolis to increase productivity of Peranakan Ongole - Budi Haryanto; Z Hasan; Kuswandi .; I-M Artika (Jurnal Ilmu Ternak dan Veteriner, 2012)
Propolis is a complex substance found in the bee hives and it has medicinal advantages for many diseases.  It contains various chemicals with specific characteristics such as anti cancer, anti virus, anti fungi and anti bacteria. Propolis contains antioxydant. Propolis from Trigona spp. was used in the present experiment. Eighteen (18) heads of PO (Ongole grade) cattle were individually fed in a flock housing and randomized to receive each feeding treatment. Propolis supplements were given in a mixture with the concentrate. Similar concentrate was fed to all individuals. Three feeding treatments, i.e., R0 = Control, without propolis, R1 = nano-propolis extracted with ethanol, and offered at 2% every 7 days, and R2 = raw propolis were applied. Concentrate intake was recorded daily by substracting the orts from the quantity of offered feed. Individual weight changes were recorded monthly before morning feeding time to calculate the average daily weight gain. The results indicated positive responses to feeding nano-propolis or raw-propolis as compared to the control group. Raw-propolis seemed to be better than the nano-propolis. Concentrate intake in the control group was higher than in the propolis supplemented group. The concentrate intake may reach 7-8 kg/head/day in average, while the average daily weight gain may reach 1 kg. The average daily weight gain of individuals supplemented with propolis were 8-11% over the control group. However, if these values were compared to the ADG of PO cattle in villages (0.6 kg/day), it was more than 30% than the general performance. It was concluded that the use of propolis, either prepared by nano-technology or just raw-propolis, can be applied to increase the PO cattle productivity. Key Words: PO Cattle, Propolis, Production, Efficiency